INSTITUTIONAL OWNERSHIP AND AGENCY CONFLICT CONTROLLING MECHANISM - Leo Indra Wardhana; Eduardus Tandelilin (Journal of Indonesian Economy and Business (JIEB), 2011)
The research investigates ownership structure in Indonesia in context of agency theory for non-financial firms listed on the Indonesian Stock Exchange for 2000-2007 periods.The uniqueness of characteristic of ownership structure in Indonesia, which is dominated by large institutional shareholders motivated researcher to examine the impact and its relationship to agency conflict and balancing off agency theory in Indonesian companies.In this condition, it is certainly indicating that the existing conflict is not between managers and owners but majority and minority. The study argues that in low level ownership, controlling institutional shareholder expropriates the minority shareholders. However, when the ownerships comes to higher level, the controlling shareholder will make agency conflict lower since monitoring hypothesis becoming relevant in such level. In other words, the study argues that nonlinear relation between agency conflict which is proxied by firm’s performance ratios and controlling institutional ownership exist. Nevertheless, the study argues that debt and dividend policy can also be used to reduce the conflict. Thus, the study also examines the simultaneous relationships among the mechanisms used to reduce agency conflict.The result indicates that when controlling institutional shareholder has significant amount of shares, they will actively monitor the manager to ensure them making value.However, when the ownership is insignificant, controlling shareholder will harm firm value due to expropriation of controlling shareholder. Therefore, nonlinear relationshipexists between controlling institutional shareholder and agency conflict. Second, debt policy and dividend policy can be used to reduce the conflict. The last, it is found thatbalancing off agency theory is not applied among all policies. The only bidirectional relationship is between institutional ownership and debt policy.Keywords: controlling institutional ownership, agency theory, balancing off agency theory, debt policy, dividend policy